Indian Tourism Industry and COVID-19: Present Scenario (Journal of Tourism and Hospitality Education, 2020)
Tourism is a backbone of economy for many countries of the world. Tourism is a big source and always helpful in generating revenue and a mean of foreign exchange. Scenario in our country is not much different and Tourism contributes to GDP of this country in a big proportion. However it’s a deep matter of concern for all the stakeholders associated with tourism industry that tourism is the most affected sector in the world due to corona virus disease (COVID-19) in the beginning of 2020.COVID-19 is spreading rapidly at an unprecedented scale across continents and has emerged as the single biggest life threatening health risk in the world has faced in modern times. Th is paper focuses on the COVID-19 issue in India and its impact on the tourism and hotel industry, the paper has some significance, as the tourism and hotel industry greatly affected by the COVID-19 crisis worldwide. India is the 7th largest country of the world and rich with various tourism resources and millions of tourists arrive annually, which contributes to the country’s GDP. The need of the hour, is to take early steps to overcome the present slowdown in tourism industry by analyzing its long term impacts at the earliest.